2021
DOI: 10.1039/d1ra08193d
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected reactivity related to support effects during xylose hydrogenation over ruthenium catalysts

Abstract: Xylose was hydrogenated over Ru on two different supports.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…For deeper characterization of the ruthenium species on the surface of MCF, the H 2 chemisorption analyses were performed [ 31 , 32 ]. Based on these measurements, the ruthenium dispersion, particle size distribution and metal surface area were estimated.…”
Section: Resultsmentioning
confidence: 99%
“…For deeper characterization of the ruthenium species on the surface of MCF, the H 2 chemisorption analyses were performed [ 31 , 32 ]. Based on these measurements, the ruthenium dispersion, particle size distribution and metal surface area were estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Ru/TiO 2 catalyst was prepared by incipient wetness impregnation followed by calcination under N 2 and reduction under H 2 and characterised by several techniques (Table S1 in ESI). The preparation and characterisation of Ru/TiO 2 catalysts was detailed in another publication from our group [35] . Briefly, characterisation results show that the catalyst is composed of nanoparticles of Ru°, weakly dispersed on a TiO 2 rutile support with a very low surface area (non‐porous material).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation and characterisation of Ru/TiO 2 catalysts was detailed in another publication from our group. [35] Briefly, characterisation results show that the catalyst is composed of nanoparticles of Ru°, weakly dispersed on a TiO 2 rutile support with a very low surface area (non-porous material). Our previous results have shown that despite of the low dispersion of ruthenium, this catalytic formulation is suitable for highly selective hydrogenation.…”
Section: Catalyst Preparation and Characterisationmentioning
confidence: 99%
“…The preparation and characterisation of Ru/TiO2 catalysts was detailed in another publication from our group. [35] Briefly, characterisation results show that the catalyst is composed of nanoparticles of Ru°, weakly dispersed on a TiO2 rutile support with a very low surface area (non-porous material). Our previous results have shown that despite of the low dispersion of ruthenium, this catalytic formulation is suitable for highly selective hydrogenation.…”
Section: Resultsmentioning
confidence: 99%